Aplikasi Teknologi Multimedia pada Bidang Pendidikan Sains dan Teknologi - R. Rizal Isnanto (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2004)
The fast growing of computer technology had been accelerating the rising of a numberof multimedia-based computer applications. The multimedia applications have been used insome areas of applications in the world, included in education and teaching.The multimedia applications in the education are as teaching software forms, providesome facilities for students to learn with getting the advantages of multimedia, for thepurposes of distance learning and education program marketting.The developing of virtual environment which completed with its virtual realityconcepts allows students to feel through their seeing, hearing, and interacting along thelearning process. Multimedia provides the great contributions. However, the conventionalteaching media are still remain required.Keywords: education multimedia, virtual reality, interactivity.